2006
DOI: 10.1086/505084
|View full text |Cite
|
Sign up to set email alerts
|

Highly ResistantSalmonellaNewport‐MDRAmpC Transmitted through the Domestic US Food Supply: A FoodNet Case‐Control Study of SporadicSalmonellaNewport Infections, 2002–2003

Abstract: Newport-MDRAmpC infection is acquired through the US food supply, most likely from bovine and, perhaps, poultry sources, particularly among persons already taking antimicrobial agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
73
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 31 publications
2
73
0
9
Order By: Relevance
“…In 1984, a strain of S. Newport with resistance to cephalosporins originating in cattle in the USA, was traced through the food chain to humans (Holmberg et al, 1984). In a US FoodNet case-control study of sporadic multiple-resistant S. Newport infections, (Varma et al, 2006) concluded that patients were more likely to have consumed uncooked ground beef or runny scrambled eggs or omelettes prepared in the home.…”
Section: Salmonellamentioning
confidence: 99%
“…In 1984, a strain of S. Newport with resistance to cephalosporins originating in cattle in the USA, was traced through the food chain to humans (Holmberg et al, 1984). In a US FoodNet case-control study of sporadic multiple-resistant S. Newport infections, (Varma et al, 2006) concluded that patients were more likely to have consumed uncooked ground beef or runny scrambled eggs or omelettes prepared in the home.…”
Section: Salmonellamentioning
confidence: 99%
“…However, antimicrobial treatment of invasive salmonellosis has been complicated by an increase in Salmonella bacteria that are resistant to antimicrobials (16,47). Additionally, several studies concluded that infections with Salmonella resistant to multiple antimicrobials, known as multidrug-resistant (MDR) Salmonella, are more invasive than infections caused by non-MDR Salmonella (20,39,61,62). Infants are at higher risk for invasive salmonellosis (63), and the incidence of laboratory-confirmed NTS in infants (children less than 1 year old) is much greater than in other age groups (17,19).…”
mentioning
confidence: 99%
“…Pulsed-field gel electrophoresis (PFGE) has been used for many years to subtype Salmonella enterica with satisfactory results (7), but MLVA has the advantages of a shorter turnaround time, additional discriminatory power, and the possibility of providing phylogenetic information to investigators. We report here the development and application of an MLVA protocol for Salmonella enterica serovar Newport, a clinically and epidemiologically important serovar characterized by multidrug resistance (5,6,9,11,14,19).…”
mentioning
confidence: 99%